2011
DOI: 10.1523/jneurosci.6433-09.2011
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor Training Maintains Normal Inhibitory Influence on Both Alpha- and Gamma-Motoneurons after Neonatal Spinal Cord Transection

Abstract: Spinal cord injuries lead to impairments, which are accompanied by extensive reorganization of neuronal circuits caudal to the injury. Locomotor training can aid in the functional recovery after injury, but the neuronal mechanisms associated with such plasticity are only sparsely known. We investigated ultrastructurally the synaptic inputs to tibialis anterior motoneurons (MNs) retrogradely labeled in adult rats that had received a complete midthoracic spinal cord transection at postnatal day 5. A subset of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 58 publications
(77 reference statements)
7
45
1
2
Order By: Relevance
“…Undirected plasticity of denervated circuits leads to the development of neuronal dysfunction in the chronic stage of injury Previous investigations in animal models of SCI documented the progressive upregulation of receptor, synapse and fibre density in spinal circuitries deprived of supraspinal input (Krenz and Weaver, 1998;Kitzman, 2006;Boulenguez et al, 2010;Ichiyama et al, 2011;Kapitza et al, 2012;Tan et al, 2012;Bos et al, 2013). In the present study, we also found a multiplicity of plastic changes in spinal segments caudal to a staggered lateral hemisection SCI.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Undirected plasticity of denervated circuits leads to the development of neuronal dysfunction in the chronic stage of injury Previous investigations in animal models of SCI documented the progressive upregulation of receptor, synapse and fibre density in spinal circuitries deprived of supraspinal input (Krenz and Weaver, 1998;Kitzman, 2006;Boulenguez et al, 2010;Ichiyama et al, 2011;Kapitza et al, 2012;Tan et al, 2012;Bos et al, 2013). In the present study, we also found a multiplicity of plastic changes in spinal segments caudal to a staggered lateral hemisection SCI.…”
Section: Discussionsupporting
confidence: 81%
“…Although previous studies reported contrasting and variable conclusions, they consistently highlighted the progressive upregulation of receptor (Murray et al, 2010), synapse (Kitzman, 2006;Ichiyama et al, 2011;Kapitza et al, 2012;Tan et al, 2012), and fibre density (Krenz and Weaver, 1998;Ballermann and Fouad, 2006;Hou et al, 2008Hou et al, , 2009) in response to the interruption of supraspinal input. Likewise, ablation of afferent pathways in the brain provokes the formation of new fibre arborizations and spines in the affected region (Kirov and Harris, 1999).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…There is also evidence that treadmill training restored a normal balance of excitatory to inhibitory synapses, thereby improving motor neuron activity [45]. Results from this study, as well as the literature, indicate that FES alone can have some benefit in improving locomotor capability, such as improved step length and improved spinal reflexes.…”
Section: Possible Influence Of Fes+rtt On Spinal Circuitrysupporting
confidence: 55%
“…The ability to modulate spinal plasticity, and resulting functional recovery, by hind-limb afferent stimuli has also been demonstrated in a number of previous studies [41][42][43]. Recent evidence that FES of cutaneous afferent pathways is effective in modulating the generation of stepping in cats and humans with SCI [44][45] could indicate that applied stimulation may enhance afferent modulation of spinal circuitry.…”
Section: Introductionmentioning
confidence: 74%